SERPINB2 and miR‐146a/b are coordinately regulated and act in the suppression of psoriasis‐associated inflammatory responses in keratinocytes. Issue 1 (13th November 2019) - Vaher, Helen; Kivihall, Anet; Runnel, Toomas; Raam, Liisi; Prans, Ele; Maslovskaja, Julia; Abram, Kristi; Kaldvee, Bret; Mrowietz, Ulrich; Weidinger, Stephan; Kingo, Külli; Rebane, Ana
Abstract: Psoriasis is a chronic inflammatory skin disease with numerous involved factors. miR‐146a and miR‐146b (miR‐146a/b) are anti‐inflammatory miRNAs that are increased in psoriatic skin. SERPINB2 has been shown to be upregulated in the inflammation and infections. Here we aimed to study the relationship between miR‐146a/b and SERPINB2 and to delineate the role of SERPINB2 in association of plaque psoriasis. We report increased SERPINB2 expression in the skin of psoriasis patients, which was in a positive relationship with psoriasis severity and in a negative relationship with miR‐146a/b in psoriatic lesions. In cultured keratinocytes, both cellular and secreted SERPINB2 levels were strongly induced in response to IFN‐γ and TNF‐α. Interestingly, SERPINB2 mRNA was downregulated by IL‐17A and the combination of TNF‐α and IL‐17A at time points when miR‐146a was increased. The predicted binding site for miR‐146a/b in 3' untranslated region of SERPINB2 revealed no activity in luciferase assay, while siRNA silencing of miR‐146a/b direct targets IRAK1 and CARD10 resulted in reduced expression of SERPINB2, suggesting that miR‐146a/b indirectly control SERPINB2 expression in the skin. The siRNA silencing of SERPINB2 increased the expression of IL‐8, CXCL5 and CCL5 and migration of neutrophils revealing its anti‐inflammatory role in keratinocytes. Our data together suggest that SERPINB2 and miR‐146a/b are part of disease‐related network of molecules that are coordinately regulated and act in controlling the inflammatory responses in psoriatic skin.